2009
DOI: 10.1111/j.1556-4029.2009.01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Characteristics of Suicide by Electrocution in Bulgaria

Abstract: Suicides by electrocution (SE) are relatively rare and insufficiently studied. The purpose of this study is to present a more detailed picture of SE in Bulgaria. Forensic medical files of 59 SE cases were examined. SPSS 11.0 software was applied to produce the descriptive statistical analyses. Values of p < 0.05 were assumed to be statistically significant. We studied 59 SE cases, which account for 6.24% of all deaths by electrocution and 0.09% of all forensic autopsies. The average age of victims was 45.19 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
11
1
Order By: Relevance
“…The incidences of death due to fatal electric injuries in our study were 2.56%, which is almost similar with the incidences observed by Gupta et al [4] (2.02%) and Rautji et al [5] (1.98%) in their studies. Incidences of death due to fatal electrocution were quite lower in the studies conducted by the foreign authors [6,7] than those reported by us. In this study, majority of the victims were men (85%) of adult age group [e.g., from 21 to 50 years (75%)], which is consistent with the findings of most of the other authors.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The incidences of death due to fatal electric injuries in our study were 2.56%, which is almost similar with the incidences observed by Gupta et al [4] (2.02%) and Rautji et al [5] (1.98%) in their studies. Incidences of death due to fatal electrocution were quite lower in the studies conducted by the foreign authors [6,7] than those reported by us. In this study, majority of the victims were men (85%) of adult age group [e.g., from 21 to 50 years (75%)], which is consistent with the findings of most of the other authors.…”
Section: Discussioncontrasting
confidence: 49%
“…In this study, majority of the victims were men (85%) of adult age group [e.g., from 21 to 50 years (75%)], which is consistent with the findings of most of the other authors. [4][5][6][7][8] We made an effort to analyze the cases according to seasonal and diurnal variations and observed a characteristic higher incidences of fatal electrocution in the season of monsoon, which is in the months of July to September in this area. These results were consistent with the observations made by Gupta et al [4] and Kumar et al [9] , whereas Shaha and Joe [10] and Sheikhazadi et al [11] found higher incidences of fatal electrocution in summer seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Electric energy is used by billions of people worldwide. However, despite the diffusion and the wide use of it, deaths related to electricity are infrequent and generally categorised as accidental (related to occupational activities 1 ), rarely as suicide electrocution (SE) [2][3][4] -in subjects with a good knowledge of electricity, probably due to their working activity 5 while other authors consider the use of electricity to be easy, so specific knowledge is not needed. 3 Homicides are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocution as a sole method of suicide is found in scientific literature, but as a part of complex suicide is rarely reported. 8–17 Alicot et al. 18 reported a case of complex suicide where the victim allegedly used multiple methods including electrocution in a bathtub along with a medicine overdose.…”
Section: Discussionmentioning
confidence: 99%